3D Virtual Worlds for interaction and communication in the online educational moment - Baños González, Miguel; Rodríguez García, Teresa C.; Rajas Fernández, Mario (Historia y Comunicación Social, 2014)
3D Virtual Worlds offer the possibility of a redesign of communication situations of traditional online education, being its potentiality to restore characteristics of classical classroom education. Here we present the design of a teaching methodology that includes the phases of action for the development of educational activities in 3D platforms as complementary resource for online education. As a result, it is confirmed the positive impact of its use in learning skills, social dimension of learning and student motivation.